Head impact exposure and concussion in women`s collegiate club lacrosse - Cecchi, N. J.; Monroe, D. C.; Fote, G. M.; Small, S. L.; Hicks, J. W. (Research in Sports Medicine, 2022)
This study sought to describe head impact exposure in women`s collegiate club lacrosse. Eleven women`s collegiate club lacrosse players wore head impact sensors during eight intercollegiate competitions. Video recordings of competitions were used to verify impact data. Athletes completed questionnaires detailing their concussion history and perceived head impact exposure. During the monitored games, no diagnosed concussions were sustained. Three athletes reported sustaining head impacts (median=0; range: 0-3 impacts per game). Six impacts registered by the sensors were verified on video across a total of 81 athlete-game exposures. Verified impacts had a median peak linear acceleration of 21.g (range: 18.3g - 48.3g) and peak rotational acceleration of 1.1 krad/s2 (range: 0.7 krad/s2 - 5.7 krad/s2). Women competing in collegiate club lacrosse are at a low risk of sustaining head impacts, comparable to previous reports of the high school and collegiate varsity levels of play.